Applying community-based participatory research principles to build trust and equity in health and socio-ecological studies in Greenland - Malory Peterson; Augustine Rosing; Elizabeth Rink; Mark Schure; Julia Haggerty; Gitte Adler Reimer; Christina Vl Larsen (International Journal of Circumpolar Health)
Community-based participatory research (CBPR) is a framework to improve social equity by engaging communities as equal partners in research design, conduct, and knowledge creation. While CBPR has seen increasing application in Arctic regions, its use in Greenland has been limited by logistical, linguistic, and historical challenges, including community fatigue from extractive research practices. This manuscript details a CBPR-informed approach used to conduct an exploratory study on fertility, reproductive health, and climate adaptation in the Kalaallit community of Paamiut. The study aimed to understand the socio-environmental factors influencing fertility decisions amid economic and environmental changes. We report on nine strategies used to conduct equitable health and socio-ecological research in Greenland guided by the principles of CBPR. Using CBPR principles improved trust, participant recruitment, and the creation of community-valued research products in Paamiut. While time and funding limitations constrained full implementation of CBPR best practices, this study highlights the potential of CBPR to improve equity in Greenlandic research. Using CBPR principles to guide community-engaged research in Greenland provides a concrete and actionable way for students or early-career researchers to promote equitable relationships despite resource limitations. The methods described can be applied across other research disciplines to continue building trust and sustainability in international research partnerships in Greenland.